2019
DOI: 10.7554/elife.41036
|View full text |Cite
|
Sign up to set email alerts
|

JNK-dependent cell cycle stalling in G2 promotes survival and senescence-like phenotypes in tissue stress

Abstract: The restoration of homeostasis after tissue damage relies on proper spatial-temporal control of damage-induced apoptosis and compensatory proliferation. In Drosophila imaginal discs these processes are coordinated by the stress response pathway JNK. We demonstrate that JNK signaling induces a dose-dependent extension of G2 in tissue damage and tumors, resulting in either transient stalling or a prolonged but reversible cell cycle arrest. G2-stalling is mediated by downregulation of the G2/M-specific phosphatas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
83
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(102 citation statements)
references
References 96 publications
(178 reference statements)
8
83
1
Order By: Relevance
“…In these cells, ROS production and p53 upregulation contribute to the activation of JNK signalling, which then induces Upd1/Upd2/Upd3 expression and secretion, leading to non-autonomous tissue growth effects (Figure 4C; Nakamura et al, 2014). A somewhat related role for JNK signalling was recently observed for cells upon wounding in wing imaginal discs -wounding induced JNK signalling, and cells became transiently "stalled" in the cell cycle at G2 phase (or near-permanently "arrested" in G2 phase after JNK induction via egr overexpression in the rotund expression domain) (Cosolo et al, 2019). Researchers found that JNK signalling induces G2 phase stalling/arrest via downregulating the activity of Stg (an inducer of mitosis) and, furthermore, that cells with this G2 profile were protected from JNK-mediated apoptosis (Cosolo et al, 2019).…”
Section: Non-autonomous Effects Of Jnk Signallingmentioning
confidence: 54%
See 3 more Smart Citations
“…In these cells, ROS production and p53 upregulation contribute to the activation of JNK signalling, which then induces Upd1/Upd2/Upd3 expression and secretion, leading to non-autonomous tissue growth effects (Figure 4C; Nakamura et al, 2014). A somewhat related role for JNK signalling was recently observed for cells upon wounding in wing imaginal discs -wounding induced JNK signalling, and cells became transiently "stalled" in the cell cycle at G2 phase (or near-permanently "arrested" in G2 phase after JNK induction via egr overexpression in the rotund expression domain) (Cosolo et al, 2019). Researchers found that JNK signalling induces G2 phase stalling/arrest via downregulating the activity of Stg (an inducer of mitosis) and, furthermore, that cells with this G2 profile were protected from JNK-mediated apoptosis (Cosolo et al, 2019).…”
Section: Non-autonomous Effects Of Jnk Signallingmentioning
confidence: 54%
“…A somewhat related role for JNK signalling was recently observed for cells upon wounding in wing imaginal discs -wounding induced JNK signalling, and cells became transiently "stalled" in the cell cycle at G2 phase (or near-permanently "arrested" in G2 phase after JNK induction via egr overexpression in the rotund expression domain) (Cosolo et al, 2019). Researchers found that JNK signalling induces G2 phase stalling/arrest via downregulating the activity of Stg (an inducer of mitosis) and, furthermore, that cells with this G2 profile were protected from JNK-mediated apoptosis (Cosolo et al, 2019). It was also shown that the G2-biased profile of clones mutant for wts or dlg1 was due to JNK signalling (Cosolo et al, 2019).…”
Section: Non-autonomous Effects Of Jnk Signallingmentioning
confidence: 65%
See 2 more Smart Citations
“…The JNK MAPK pathway is involved in many cellular processes, such as cell growth, differentiation, migration, apoptosis, and inflammatory and immune responses. It has also been implicated in many pathological conditions, including cancer, stroke, heart disease, and inflammatory disease (Coffey, 2014;Yuan et al, 2017;Blum et al, 2019;Cosolo et al, 2019). Studies show that JNK plays a vital role in the whole metastatic process.…”
Section: Discussionmentioning
confidence: 99%